'My Car is the Best Thing That Ever Happened to Me': Automobility and Novice Drivers in Iceland. (May 2014) - Collin-Lange, Virgile
A survey submitted to Icelandic novice drivers and the author's personal experience of obtaining the drivers licence constitute the ground basis for this article. In their responses, many of the young people who answered the survey pointed out that their car use was an adaptation to the conditions in which they found themselves: a pervasively car-oriented transport system. Their car use is also symptomatic of how they approach their own automobility and spatiality. The present article concurs with current discussions of automobility and approaches it as a regime. The author argues, however, that one's integration into the regime of automobility is an expression of human territoriality. This article also shows that automobility should be considered as a phase during which one's individual motility is maximized according to the structural and social environments in which the individual finds himself or herself. Finally this article calls for greater considerations about youth within the field of mobilities.